2021
DOI: 10.1002/ejoc.202001608
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Rearrangement of 2‐(2‐Aminobenzyl)furans: Synthesis of Functionalized Indoles and Carbazoles

Abstract: Igor V. Trushkov, [e, f] and Maxim G. Uchuskin* [a] 2-(2-Acylvinyl)indoles obtained by oxidative rearrangement of substituted 2-(2-aminobenzyl)furans could be used to construct structural analogues of antifungal alkaloids caulindoles AÀ D as well as other indole-derived molecules and substituted carba-zoles by introducing new reaction centers into the structure of starting materials or by synthetic manipulation with functional groups of the obtained compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Initially we screened a series of oxidants, commonly applied for performing related processes, and found that the use of N -bromosuccinimide (NBS)/pyridine system in aq. THF leads to the formation of ( E )- 2a with 77% yield while application of m -chloroperbenzoic acid ( m -CPBA) afforded ( Z )- 2a [ 33 ] as the exclusive product in 87% yield ( Scheme 2 ) [ 34 , 35 ]. Other oxidants (ceric ammonium nitrate, pyridinium chlorochromate, 2,3-dichloro-5,6-dicyanobenzoquinone, Oxone, NaClO 2 , MnO 2 , and Pb(OAc) 4 ) led to similar results, but with a lower conversion of the starting compound 1a or in low yield and poor Z , E -ratio of triketone 2a .…”
Section: Resultsmentioning
confidence: 99%
“…Initially we screened a series of oxidants, commonly applied for performing related processes, and found that the use of N -bromosuccinimide (NBS)/pyridine system in aq. THF leads to the formation of ( E )- 2a with 77% yield while application of m -chloroperbenzoic acid ( m -CPBA) afforded ( Z )- 2a [ 33 ] as the exclusive product in 87% yield ( Scheme 2 ) [ 34 , 35 ]. Other oxidants (ceric ammonium nitrate, pyridinium chlorochromate, 2,3-dichloro-5,6-dicyanobenzoquinone, Oxone, NaClO 2 , MnO 2 , and Pb(OAc) 4 ) led to similar results, but with a lower conversion of the starting compound 1a or in low yield and poor Z , E -ratio of triketone 2a .…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of carbazoles generally follows two distinct approaches ( Figure 2 ): (a) an annulation reaction to generate the central pyrrole ring or (b) a benzannulation reaction in which a benzene ring is appended on the five-member ring of an indole [ 15 , 16 , 17 , 18 , 19 ]. While several syntheses have been reported [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], the abundant presence of the carbazole core in bioactive molecules and photoelectronic materials makes them attractive targets for the development of new synthetic methodologies, often targeting new substitution patterns, modularity and mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%